Clinical and functional characterization of the Pro1198Leu ABCC8 gene mutation associated with permanent neonatal diabetes mellitus. Issue 3 (11th March 2013) - Takagi, Tomoyuki; Furuta, Hiroto; Miyawaki, Masakazu; Nagashima, Kazuaki; Shimada, Takeshi; Doi, Asako; Matsuno, Shohei; Tanaka, Daisuke; Nishi, Masahiro; Sasaki, Hideyuki; Inagaki, Nobuya; Yoshikawa, Norishige; et al.
Abstract Aims/Introduction The adenosine triphosphate (ATP)‐sensitive potassium (KATP) channel is a key component of insulin secretion in pancreatic β‐cells. Activating mutations in ABCC8 encoding for the sulfonylurea receptor subunit of the KATP channel have been associated with the development of neonatal diabetes mellitus (NDM). The aim was to investigate clinical and functional characterization of the Pro1198Leu ABCC8 gene mutation associated with permanent NDM (PNDM). Materials and Methods The coding regions and conserved splice sites of KCNJ11, ABCC8 and INS were screened for mutations in a 12‐year‐old girl diagnosed with PNDM. The functional property of the mutant channel identified was examined with patch‐clamp experiments in COS‐1 cells. We also investigated the difference of effectiveness between two groups of oral sulfonylureas in vitro and in the patient. Results We identified a heterozygous missense mutation (c.3593 C>T, Pro1198Leu) in ABCC8. The mutated residue (P1198) is located within a putative binding site of sulfonylureas, such as tolbutamide or gliclazide. In patch‐clamp experiments, the mutant channel was less ATP sensitive than the wild type. Furthermore, the sensitivity to tolbutamide was also reduced in the mutant channel. In addition to the tolbutamide/gliclazide binding site, glibenclamide is thought to also bind to another site. Glibenclamide was more effective than other sulfonylureas in vitro and in the patient. The treatment of the patient was finally able to be switched from insulin injection to oral glibenclamide. Conclusions We identified the Pro1198Leu ABCC8 mutation in a PNDM patient, and clarified the functional and clinical characterization. The present findings provide new information for understanding PNDM.